Sudden death and exercise - Noakes, T. D. (Sportscience)
The content of this study: - Historical Background, - Effect of Exercise on Risk of Sudden Death, - Levels of Physical Fitness, - Warning Symptoms, - Factors Triggering Events, - Exercise as a Protective Mechanism, - Screening for Risk Factors. Summary: Sudden death in athletes will always be an emotive topic, for it suggests that athleticism may not prevent the development of heart disease and may actually increase the likelihood that the athlete will die suddenly during exercise. Persons who die suddenly during exercise have advanced heart disease of which they are frequently unaware. The commonest forms of heart disease associated with sudden death during exercise are coronary artery disease and hypertrophic cardiomyopathy. Less common cardiac conditions linked to sudden death in athletes include anomalous origin of the coronary arteries, aortic rupture associated with Marfan's syndrome, myocarditis, mitral valve prolapse and various arrhythmias. The incidence of these predisposing diseases in the athletic population is extremely low, possibly of the order of 1 per 10,000 to 1 per 200,000 athletes. Detection of some of these conditions in asymptomatic athletes may be difficult, if not impossible. Regular exercise reduces the overall risk of sudden death in persons with latent coronary artery disease, yet acutely increases the risk of sudden death during exercise for those with heart disease that predisposes to sudden death. In practical terms, only athletes with symptoms or clinical signs of, or risk factors for coronary or other forms of heart disease should undergo routine maximal exercise testing when they commence an exercise training program. However, once symptoms suggestive of cardiac disease are present in athletes, detailed cardiological testing is mandatory.